Audiovisual narrative, re-enactment, and historical education: Hospitals in the Spanish Civil War - Hernàndez-Cardona, Francesc Xavier; Feliu-Torruella, Maria; Sospedra-Roca, Rafael; Boj-Cullell, Isabel (Frontiers in Education, 2022)
Audiovisual narrative is a widely used resource in the presentation of diverse historical content. Historical recreation, thanks to its ability to generate images of the past, when combined with the use of emerging digital technologies (CGI Computer-Generated Imagery), allows optimization of audiovisual narratives that present images and contexts of the past and its heritage. From a perspective of promoting historical thought, high school and higher education students can take part in initiatives of historical recreation (in the key to service learning). This process allows its incorporation into the production of educational history products, which can be reapplied in formal and non-formal teaching-learning spaces. The experience developed by the DIDPATRI group (Heritage Didactics) of the University of Barcelona (2017-2021) based on projects set in the health problems of the Spanish Civil War, has generated guidelines for the development of a digital audiovisual narrative of didactic character based on activities of historical recreation and service learning in contexts of public history and archaeology.